The effects of sodium bicarbonate in the lactate concentration and in the performance of middle distance runners and long distance. - Aquino, David Costa de (2011)
The Objective of this study was to analyze and to compare the effects of the ingestion sodium bicarbonate in the performance of middle distance runners and long distance and at the concentration of sanguine lactate, observing the possible alterations in the heart frequency. In this study were considered six middle distance runners and long distance, of medium age of 33.8 ± 6.2, weight 58.2 ± 6.8, and height 1.69 ± 8.0 and 8.5 ± 4.5) years of training. All athletes well conditioned physically, who train six days a week, with a weekly volume that oscillates among 80 and 100 km during the period of specific preparation. The athletes were submitted two sessions of interval training, in different days, being 10 x 400 meters with passive pause of 60 seconds, in the first day the athletes were analyzed without the supplement and in the second day they made the ingestion of 0.3g/kg sodium bicarbonate. The results at the performance of the athletes changed from 0.3 to 3.8% with average of 1.46% and in the lactate concentration a medium increase of 49%, with variation among the athletes from -7% to 83%. The heart frequency of rest, exercise and powders didn't suffer significant alterations at the average of the groups. It was based on in these results we can conclude that the ingestion of sodium bicarbonate is beneficial in the improvement of the performance of middle distance runners and long distance and that provokes an increase at the concentration of sanguine lactate.